2010
DOI: 10.1111/j.1939-1676.2010.0490.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Characteristics and Topographic Distribution of Focal Atrial Tachycardias in Dogs

Abstract: Background: Focal atrial tachycardia (FAT) is a common supraventricular tachycardia in dogs.Objective: To evaluate electrophysiologic characteristics and topographic distribution of FAT. Animals: Sixteen dogs with symptomatic FAT. Methods: Retrospective case series. Electrophysiological studies were performed to test the inducibility of documented and no documented arrhythmias. Once induced for each dog, FAT was analyzed for electrogenic mechanism, endocardial electrogram, and location.Results: Nineteen FATs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Although the incidence of focal atrial tachycardia in humans is reported to occur in 10% of patients with supraventricular tachycardias, focal atrial tachycardia is more common in dogs . Of interest, the distribution of sites at which the majority of focal ATs arise is the same in both dogs and man . For example, both species show that the focal ATs arise commonly at the crista terminalis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of focal atrial tachycardia in humans is reported to occur in 10% of patients with supraventricular tachycardias, focal atrial tachycardia is more common in dogs . Of interest, the distribution of sites at which the majority of focal ATs arise is the same in both dogs and man . For example, both species show that the focal ATs arise commonly at the crista terminalis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of the electrogenic mechanism of a supraventricular tachycardia can be only made by endocardial mapping (5,9,11). The use of surface ECG and Holter monitoring provide only a suspicious of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In human beings, paroxysmal SVT is closely associated with paroxysmal AF and it has been suggested that SVT might predispose to AF development because of atrial stretch, reduced atrial refractoriness and vagal activation during tachycardia (Chang et al, 2008). Focal atrial tachycardia (FAT) was reported in two DdB in a series of 16 dogs diagnosed with FAT by electrophysiological study (Santilli et al, 2010). Seven of these dogs had a surface ECG diagnosis of AF.…”
Section: Accepted Manuscriptmentioning
confidence: 99%